[tex]a)\\a = 4 \ cm\\\\P = \frac{a^{2}\sqrt{3}}{4} = \frac{4^{2}\cdot\sqrt{3}}{4} = 4\sqrt{3} \ cm^{2}[/tex]
[tex]b)\\a = 2\sqrt{3} \ cm\\\\P = \frac{a^{2}\sqrt{3}}{4} = \frac{(2\sqrt{3})^{2}\cdot\sqrt{3}}{4} = \frac{12\sqrt{3}}{4} = 3\sqrt{3} \ cm^{2}[/tex]
[tex]c)\\h = \frac{a\sqrt{3}}{2}\\oraz\\h = 6\sqrt{3} \ cm\\\\\frac{a\sqrt{3}}{2} = 6\sqrt{3} \ \ /\cdot2\\\\a\sqrt{3} = 12\sqrt{3} \ \ /:\sqrt{3}\\\\a = 12 \ cm[/tex]
[tex]P = \frac{a^{2}\sqrt{3}}{4} = \frac{12^{2}\cdot\sqrt{3}}{4} = \frac{144\sqrt{3}}{4} = 36\sqrt{3} \ cm^{2}[/tex]